2018
DOI: 10.3389/fmicb.2018.02407
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Prevents EV-D68 Replication by Inhibiting the Acidification of Virus-Containing Endocytic Vesicles

Abstract: Enterovirus D68 (EV-D68) has emerged as a significant respiratory pathogen that can cause severe respiratory disease and acute neurologic disease. At present, there are no approved antiviral agents or vaccines for EV-D68. In this study, we demonstrate that andrographolide (ADO), an active component of Andrographis paniculata, exerts substantial antiviral activity against EV-D68 infection. ADO treatment dramatically inhibited EV-D68 RNA replication (EC50 = 3.45 μM) and protein synthesis without producing signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Andrographolide, the main active component isolated from the extract of the herb andrographis paniculata, has a wide range of biological activities including immunity regulation, anti-virus, anti-bacteria, antiparasite, anti-tumor, and anti-hyperglycemia [113,114]. Previous studies have shown that andrographolide has a broad spectrum of antiviral properties, which inhibits various virus infections including influenza A virus (IAV) [115], human immunodeficiency virus (HIV) [116], Chikungunya virus (CHIKV) [117], dengue virus (DENV) [118,119], and Enterovirus D68 (EV-D68) [120]. Atchara Paemanee et al suggested that andrographolide may exert broad-spectrum antiviral activity by interfering a variety of cellular pathways (including autophagy, unfolded protein response (UPR) pathway and oxidative stress, etc.).…”
Section: Andrographolidementioning
confidence: 99%
“…Andrographolide, the main active component isolated from the extract of the herb andrographis paniculata, has a wide range of biological activities including immunity regulation, anti-virus, anti-bacteria, antiparasite, anti-tumor, and anti-hyperglycemia [113,114]. Previous studies have shown that andrographolide has a broad spectrum of antiviral properties, which inhibits various virus infections including influenza A virus (IAV) [115], human immunodeficiency virus (HIV) [116], Chikungunya virus (CHIKV) [117], dengue virus (DENV) [118,119], and Enterovirus D68 (EV-D68) [120]. Atchara Paemanee et al suggested that andrographolide may exert broad-spectrum antiviral activity by interfering a variety of cellular pathways (including autophagy, unfolded protein response (UPR) pathway and oxidative stress, etc.).…”
Section: Andrographolidementioning
confidence: 99%
“…Several strains listed in Table 2 of small (+)ssRNA-containing viruses, pico-rna-viruses, in the family Picornaviridae, including equine rhinitis A virus (ERAV) in the genus Aphthovirus; [84][85][86]; EMCV has a wide host range including humans [87]; and low-neurovirulent TMEV is a mouse pathogen that is able to cause a chronic demyelinating disease and is thus used for studies on human multiple sclerosis [88] as shown in Table 2. The viral capsid of the picornaviruses comprises three virion proteins (VP1, VP2, and VP3) that form the shell and one virion protein (VP4) lying on the inner surface of the virus particle as illustrated in Fig.…”
Section: Picornaviridaementioning
confidence: 99%
“…Typically, binding of the viral capsid proteins of picornaviruses to receptors triggers endocytosis. When the endosome becomes acidic, the viral capsids undergo conformational change and/or a protease is activated, resulting in channel formation that allows the viral genome to pass through the host cytosol [84,93], except for EMCV and poliovirus for which it remains unclear whether their genomes can directly penetrate through the plasma membrane due to no requirement of low pH for infection [93,94]. Information on which virus strains require Sia and which sialyl glycan structure is a determinant for viral attachment and infection is critical to understand virus tropism and pathogenesis for diagnosis and treatment, especially the design of a detection system and inhibitors targeting Sia-binding sites in viral lectins.…”
Section: Picornaviridaementioning
confidence: 99%
See 1 more Smart Citation
“…The antiviral efficacy of pyrazolo[3,4-d]pyrimidines have also been evaluated against enteroviruses; CV-B3 and EV-A71 virus infections where they inhibited their infections but the exact mechanism was not established [181]. More recently, andrographolide has been reported to suppress EV-D68 replication targeting the viral maturation within the acidified endosomes [182]. World Health organization (WHO) recommended combination therapy has also been evaluated for possible antiviral development against enteroviruses [183].…”
Section: Introductionmentioning
confidence: 99%